Review of prime issues in big data storage - Zhi Zhou; Javad Pourqasem; Shadi Sayadmanesh (Big Data and Computing Visions)
Developing the scale and increasing the data set, make the reliability and availability principal affairs to access process and data achievement. In addition, we face the challenges of handling big data in terms of storage and management. This paper provides the important issues related to the massive storage systems, distributed storage systems, and big data storage mechanisms. Then we present some analysis models utilizing in big data and describe structure of them in details.